(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied a mathematical framework of higher-order multipole fields in the vicinity of optical nanoantennas. We have exemplified at suitably chosen Nanoantennas i.e. a Nano antenna which strongly enhances the quadruple field. The modification of excitation rates in quantum mechanical systems due to this quadrupolar enhancement was studied. The hybrid system consisting of an optical Nano antenna and a quantum mechanical three level system was studied in detail. A properly designed Nano-antenna can excite dipole for bidden transitions in three level systems due to the enhanced higher order multipole fields. The dynamics of the system is strongly altered by the presence of the nanoantenna and cannot be done by the quadrupolar enhancement alone. This can be achieved by enhancing higher order multipole fields near the antenna. A quadrupole transition as the dominant excitation channel in a three level system was considered. It was found that the enhancement of this transition significantly intensify subsequent emission processes with respect to altered emission characteristics. The effects depend on geometrical parameters; the properties of the optical nanoantenna can be tailored and hence allowed for direct implementations in spectroscopies schemes. The obtained results were found in good agreement with previously obtained results.